Impact of Substituents and Nonplanarity on Nickel and Copper Porphyrin Electrochemistry: First Observation of a Cu-II/Cu-III Reaction in Nonaqueous Media - SENGE, MATHIAS (My University, 2014)
ABSTRACT Electrochemical studies of the oxidation of dodecasubstitued and highly nonplanar nickel porphyrins in a non-coordinating solvent have previously revealed the first NiIII porphyrin dication. Herein, we investigate if these nonplanar porphyrins can also be used to detect the so far unobserved CuIII porphyrin dication. Electrochemical studies of the oxidation of (DPP)M and (OETPP)M show three processes, the first two of which are macrocycle centered to give the porphyrin dication followed by a CuII/III processes at more positive potential. Support for the assignment of the CuII/III process comes from the linear relationships observed between E1/2 and the third ionization potential of the central metal ions for Fe, Co, Ni and Cu complexes of (DPP)M and (OETPP)M. In addition, the oxidation behaviour of additional nonplanar nickel porphyrins is investigated in a non-coordinating solvent, with nickel meso-tetraalkylporphyrins also being found to form NiIII porphyrin dications. Finally, examination of the nickel mesotetraalkylporphyrins in a coordinating solvent (pyridine) reveals that the first oxidation becomes metal-centered under these conditions, as previously noted for a range of nominally planar porphyrins.
PUBLISHED
Keywords: nonplanar nickel porphyrins; nonplanar nickel porphyrins